A camera orientating device using compliant mechanism for autonomous mobile robots - Hoang Ngoc Phuong; Nguyen Quoc Van; Pham Huy Tuan (Journal of Technical Education Science, 2019)
This paper presents the design of a compliant bio-inspired camera-positioning mechanism. The device combines human muscle actuation scheme and spherical mechanism with the aim of miniaturizing the orienting mechanism. The active orientation system which has two degrees of freedoms (pan and tilt) is synthesized by using a compliant mechanism. The flexible mechanisms utilize the deflection of curved beams to drive the orienting modules. A shape and size optimization process using genetic an algorithm is used for the design. The objectives of the optimization problem are to maximize the orienting angles and maximize the linearity of the linear input and angular output relation. To demonstrate the feasibility of the optimum design, finite element analysis using ABAQUS is carried out and a prototype is also fabricated using CNC laser cutting method. The experimental results show that the proposed design exhibits essential characteristics of a camera orientation a system such as lightweight, compactness and high precision